UJI AKTIVITAS EKSTRAK ETANOL BAWANG PUTIH (Alliumsativum L.)YANG DIHITAMKAN SEBAGAI ANTI INFLAMASI YANG DIINDUKSI OLEH KARAGENAN TERHADAP Mus musculus - Wiratma, Dicky Yuswardi; Manurung, Kesaktian; Supartiningsih, Supartiningsih; Telaumbanua, May Fransisca (UNIVERSITAS SARI MUTIARA INDONESIA, 2017)
One of the plants used as an alternative to traditional medicine is Garlic (Allium sativum L.). Garlic which is rich in organic organo sulfur compounds (amino acids and essential oils) in the form of allin has many benefits in treating various types of diseases. One of the processed forms of garlic is black garlic. Black garlic is a heating product from garlic that is heated at a temperature of 70oC with a relative humidity of 70-80%. This study aims to determine the use of black garlic as an anti-inflammatory, how to make black garlic and at what concentration black garlic has an anti-inflammatory effect. The method used in this research is a pure experimental method. The results of the %R measurement, the negative control group had the highest level of inflammation and the lowest was the black garlic extract group with a concentration of 60%. Meanwhile, in the %IR measurement, the black garlic extract group with a concentration of 60% had the greatest ability to block inflammation. From the tests that have been carried out, black garlic is obtained from heating results and the results of measuring the effectiveness of its anti-inflammatory activity, namely black garlic extract with a concentration of 60% have a better anti-inflammatory effect compared to other concentrations and diclofenac sodium.